2022
DOI: 10.3233/bme-211371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of casein phosphopeptide amorphous calcium fluoride phosphate and calcium glycerophosphate on incisors with molar-incisor hypomineralization: A cross-over, randomized clinical trial

Abstract: BACKGROUND: Within the scope of minimally invasive dentistry, the use of different biocompatible remineralization agents on incisors affected by molar-incisor hypomineralization (MIH) gains importance. OBJECTIVE: To evaluate the effect of casein phosphopeptide amorphous calcium fluoride phosphate (CPP-ACFP) and calcium glycerophosphate (CaGP) in mineral density (MD) of white/creamy and yellow/brown demarcated opacities on incisors affected by MIH by means laser fluorescence (LF). METHODS: As a cross-over, rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A comparison between the studies presented in Table 1 is difficult because many different techniques were used to measure the remineralizing effect on MIH-teeth, e.g., microcomputed tomography [ 25 ], transverse microradiography [ 23 ], microhardness test (Vickers) [ 42 ], laser fluorescence [ 46 , 47 , 48 ], Raman microscopy [ 43 ], energy dispersive spectroscopy [ 44 ], or scanning electron microscopy [ 28 ]. In most clinical studies, laser fluorescence was used to measure the in vivo remineralization effect ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…A comparison between the studies presented in Table 1 is difficult because many different techniques were used to measure the remineralizing effect on MIH-teeth, e.g., microcomputed tomography [ 25 ], transverse microradiography [ 23 ], microhardness test (Vickers) [ 42 ], laser fluorescence [ 46 , 47 , 48 ], Raman microscopy [ 43 ], energy dispersive spectroscopy [ 44 ], or scanning electron microscopy [ 28 ]. In most clinical studies, laser fluorescence was used to measure the in vivo remineralization effect ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…One other fluoride-free calcium-phosphate active ingredient that should have been considered but not included in the search was calcium glycerophosphate (CaGP), an active ingredient mentioned in the review by Enax et al [ 172 ] on the remineralization strategies of molar incisor hypocalcification. While this ingredient is used mainly to fortify fluoride toothpaste, it has only been tested in three clinical trials as an active ingredient without fluoride [ 173 , 174 , 175 ]. In those recent trials, it has been shown to be effective on its own and should really be counted as the fifth active ingredient for fluoride-free calcium-phosphate-containing toothpaste with the potential to reverse white spot lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, approaches to increasing mineral content have been investigated in the treatment of both white spot lesions and hypomineralized lesions observed in MIH and other developmental enamel defects [73,74]. In two different randomized in vivo studies by Sezer et al [75,76], the effects of different remineralization agents on white/creamy or yellow/brown demarcated opacities on the incisors affected by MIH were evaluated using the laser fluorescence method. As a result of the first study [75] using calcium glycerophosphate (CaGP), CPP-ACFP, and fluoridated toothpaste (as the control group), it was reported that agents containing CaGP and CPP-ACFP in addition to routine oral hygiene practices increased the mineral content of the lesions.…”
Section: Approaches To Increasing Mineral Contentmentioning
confidence: 99%
“…As a result of the first study [75] using calcium glycerophosphate (CaGP), CPP-ACFP, and fluoridated toothpaste (as the control group), it was reported that agents containing CaGP and CPP-ACFP in addition to routine oral hygiene practices increased the mineral content of the lesions. In the second study [76], patients used remineralization agents containing CaGP and CPP-ACFP in a cross-over design. It was reported that both agents increased the mineral content and provided remineralization after three months, regardless of the cross-over design.…”
Section: Approaches To Increasing Mineral Contentmentioning
confidence: 99%